Enhanced photoluminescence characteristics and intrinsic ferromagnetism in Co-substituted CeO2 nanoparticles. (1st March 2021) - Poornaprakash, B.; Subramanyam, K.; Kumar, Mirgender; Kim, Y.L.; Pratap Reddy, M. Siva
Abstract: The creation of oxide based magnetic materials has attracted a great deal of scientific attention, owing to their novel applications in optoelectronic, memory, and spintronic device applications. In this study, the authors report upon the structural, optical, and magnetic properties of Co-substituted CeO2 nanocrystals synthesized via the wet chemical precipitation method. The obtained nanoparticles show good crystallinity as well as an FCC structure with an Fm3m space group of host CeO2 lattice, as confirmed by an X-ray diffraction results. It is noted that Co substitution at low concentrations enhances the photoluminescence characteristics of CeO2 nanoparticles, while higher concentrations significantly reduce the intensity of PL emission, as revealed by PL studies. The estimated M − H loops illustrate that pristine CeO2 shows a paramagnetic nature, while all Co-substituted samples were ferromagnetic in nature. Furthermore, magnetic parameters such as saturation magnetization (MS ) and residual magnetization (MR ) increased with the inclusion of Co content, reaching a maximum at 4 at% Co and quenching at 6 at% and 8 at% of Co-substitution. In particular, Ce1-x Cox O2 (x = 0.04) nanoparticles show better luminescence and magnetic characteristics than the remaining concentrations. Highlights: Ce1-x Cox O2 NPs were prepared by a simple co-precipitation route. Structural, optical, and PL properties were systematically analyzed. Dopant induced RTFM was well explained through the F- center exchange mechanism.